Art therapy and eating disorders : the self as significant form - Rabin, Mury (Columbia University Press, 2003)
Art Therapy and Eating Disorders is a step-by-step approach to a new and extremely promising technique for treating people with eating disorders--children as well as adults, male and female sufferers alike--that has proven to be a crucial aid to identification, prevention, and intervention. Mury Rabin demonstrates how her award-winning art therapy technique, known as Phenomenal and Nonphenomenal Body Image Tasks or "PNBIT," can be used by clinicians other than art therapists and shows its effectiveness in combination with diverse therapeutic techniques. Unlike traditional therapy programs that treat symptoms, this technique focuses on root causes and consists of a series of tasks--some phenomenal: weight recording, mirror viewing, and body dimension estimates; others not: chromatic family line drawings and body image mandalas. The book includes five case studies that illustrate how the PNBIT technique functions in practice.